Social Media as a Digital Showcase: Brand Awareness and Its Implications for the Purchasing Decisions of MSME Products in Jakarta - Firdaus, Panca Maulana; Muhdaliha, Eryco (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The growth of social media has driven shifts in the marketing strategies of Micro, Small, and Medium Enterprises (MSMEs), particularly in urban areas like Jakarta. Here, social media no longer functions merely as a promotional tool but also serves as a digital showcase for displaying products and building brand perception. This research aims to analyze the influence of social media utilization on the purchasing decisions of MSME products in Jakarta, with brand awareness as the mediating variable. This study employs a quantitative approach using a survey method targeting 120 culinary-sector MSME actors who actively utilize social media in their marketing activities. The research data were analyzed using Partial Least Squares-based Structural Equation Modeling (SEM) with the assistance of the SmartPLS 3.0 software. The results indicate that social media utilization has a positive and significant influence on brand awareness and also has a direct effect on purchasing decisions. Furthermore, brand awareness is proven to act as a mediating variable in the relationship between social media utilization and purchasing decisions. These findings suggest that social media, as a digital showcase, plays a strategic role in building brand awareness and driving the purchase decisions for MSME products. This research is expected to provide a theoretical contribution to the development of digital marketing studies for MSMEs, as well as practical implications for MSME actors in designing effective social media-based marketing strategies.